Potensi Ekstrak n-Heksana dan Ekstrak Etanol dari Daun Sirih (Piper betle Linn) Sebagai Penghilang Bau Mulut yang Disebabkan Bakteri Staphylococcus aureus: Potential of n-Hexane and Ethanol Extract from Betel Leaves (Piper betle Linn) as a Mouth Remover Caused by Bacteria Staphylococcus aureus - Nunung Kurniasih; Assyifa Junitasari; Lilis Nurjanah; Anggita Rahmi Hafsari (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
The mouth is an ideal place for the growth and development of microorganisms because the mouth has moisture and a regular intake of food. Microbes found in the mouth, namely Staphylococcus aureus which can cause bad breath, one type of plant that is used as a bad breath remover is betel leaf. Betel leaf (Piper betle Linn) contains chavikol and betlephenol which can inhibit bacterial growth. This study aims to identify the class of compounds in betel leaf that have potential as antibacterial properties against S. aureus bacteria. The betel leaf was dried, then crushed to expand the surface of the sample (simplicia). Simplicia as much as 300 grams of macerated stratified with n-hexane, ethyl acetate and ethanol. The result was evaporated and the weight of each extract was 6.4371 g (n-hexane), 8.8007 g (etylacetate) and 9.2173 g (ethanol). Phytochemical tests and thin layer chromatography (TLC) using eluent n-hexane and ethyl acetate (8: 2) showed that n-hexane extract was thought to contain flavonoids, ethyl acetate extract containing saponins and ethanol extract containing polyphenols. Antibacterial activity test was carried out by using the paper disc diffusion method. Both the n-hexane extract and the ethanol extract of betel leaf showed very strong antibacterial activity, characterized by a diameter of inhibition above 20 mm.